2015
DOI: 10.1108/ijilt-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting elementary student teachers’ technology acceptance

Abstract: The current study sets out to identify determinants affecting tertiary students' behavioural intentions to use mobile technology in lectures. The study emphasises that the reason for using mobile technology in classrooms with large numbers of students is to facilitate interactions among students and lecturers. The proposed conceptual framework has four main antecedents of behavioural intention: system perception, intrinsic motivation, system and information quality, and uncertainty avoidance. Sample data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This finding suggests that the program could have increased TCs' expectation that others will view them as higher in status or with better teaching ability if they use technology in the classroom. This finding is in line with a previous study, in which TCs anticipated using technologies in their future classroom when they felt that others expected them to do so (Anderson & Groulx, 2015). Possible explanations for the differences between TCs and current teachers are that TCs in this program value technology more highly than current elementary school teachers, or that current elementary school teachers may not use technology as often.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggests that the program could have increased TCs' expectation that others will view them as higher in status or with better teaching ability if they use technology in the classroom. This finding is in line with a previous study, in which TCs anticipated using technologies in their future classroom when they felt that others expected them to do so (Anderson & Groulx, 2015). Possible explanations for the differences between TCs and current teachers are that TCs in this program value technology more highly than current elementary school teachers, or that current elementary school teachers may not use technology as often.…”
Section: Discussionsupporting
confidence: 89%
“…They confirmed that SE is one of the important aspects that would impact the teachers' adoption of ICT. Anderson and Groulx (2015), in their study, evaluated the intrinsic factors related to the teachers' intentions to adopt and incorporate technology in their classrooms. The findings of the study explained that 65 percent of the variation in the intention of the respondents was because of the subjective norm and the PEOU.…”
Section: Teachers' Motivation To Adopt Technologymentioning
confidence: 99%
“…Second, even though globally the number of computers in schools has increased, technology acceptance and use in the classroom and learning remains relatively low (Holden, Ozok, & Rada, 2008). Specifically, one study (Anderson & Groulx, 2015) concluded that extensive technology acceptance and use on school campuses remains largely uncommon. This suggests that the use of the technology available in education is still not fully utilised in learning.…”
Section: Global Problem Statementmentioning
confidence: 99%